The Algonquin Provincial Park Oral History Transcription Pilot Project - McElgunn, Hannah; Hunter, R.; Welsh, Emily (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
⁠⁠⁠⁠⁠⁠⁠This communication details an emerging partnership between the collections coordinator of the Algonquin Provincial Park Archives and Collections (APPAC), and anthropologists at Queen’s University in Kingston, Ontario, and Brown University in Providence, Rhode Island. This partnership offers students at Queen’s practical experience in working with oral histories, including transcription and basic discourse analysis, by engaging directly with recordings accessioned at the APPAC. In this article, we reflect on the collaborative process that gave rise to this project, outline what worked well, suggest ways to improve upon our pilot efforts, and provide a working model for other interdisciplinary partnerships focused on archival collections. We also suggest ways that archival collections can be used in interdisciplinary pedagogy and reflect on how these kinds of collaborations can be fruitful for academic researchers, archival users, students, and museum visitors.